The MK2 cascade mediates transient alteration in mGluR‐LTD and spatial learning in a murine model of Alzheimer's disease. Issue 10 (22nd September 2022) - Privitera, Lucia; Hogg, Ellen L.; Lopes, Marcia; Domingos, Luana B.; Gaestel, Matthias; Müller, Jürgen; Wall, Mark J.; Corrêa, Sonia A. L.
Abstract: A key aim of Alzheimer disease research is to develop efficient therapies to prevent and/or delay the irreversible progression of cognitive impairments. Early deficits in long‐term potentiation (LTP) are associated with the accumulation of amyloid beta in rodent models of the disease; however, less is known about how mGluR‐mediated long‐term depression (mGluR‐LTD) is affected. In this study, we have found that mGluR‐LTD is enhanced in the APPswe /PS1dE9 mouse at 7 but returns to wild‐type levels at 13 months of age. This transient over‐activation of mGluR signalling is coupled with impaired LTP and shifts the dynamic range of synapses towards depression. These alterations in synaptic plasticity are associated with an inability to utilize cues in a spatial learning task. The transient dysregulation of plasticity can be prevented by genetic deletion of the MAP kinase‐activated protein kinase 2 (MK2), a substrate of p38 MAPK, demonstrating that manipulating the mGluR‐p38 MAPK‐MK2 cascade at 7 months can prevent the shift in synapse dynamic range. Our work reveals the MK2 cascade as a potential pharmacological target to correct the over‐activation of mGluR signalling. Abstract : Disruption of synapse potentiation is associated with cognitive impairment in Alzheimer's disease (AD), yet the mechanisms mediating this dysfunction remain unknown. We showed that over‐activation of mGluR‐LTD shifts the synaptic capacity range towards depression and genetic deletion of MK2 in AD corrects over‐activation of mGluR‐LTD and restores the depressed synaptic range to normal level.